Efficient Electrocatalytic Oxygen Evolution at Extremely High Current Density over 3D Ultrasmall Zero‐Valent Iron‐Coupled Nickel Sulfide Nanosheets. Issue 24 (25th October 2018) - Cheng, Xiaodi; Lei, Chaojun; Yang, Jian; Yang, Bin; Li, Zhongjian; Lu, Jianguo; Zhang, Xingwang; Lei, Lecheng; Hou, Yang; Ostrikov, Kostya (Ken)
Abstract: Nonprecious water oxidation electrocatalysts that perform well at high current densities are among the key enabling drivers of renewable energy technologies. Herein, we report a novel strategy to produce 3D ultrasmall zero‐valent iron‐coupled nickel sulfides nanosheets (Fe 0 −Nix Sy ) hybrid on self‐supported conductive Ni foam (denoted as Fe 0 −Nix Sy /NF) through a robust single‐step gas–solid reaction. In this 3D hybrid, the Fe 0 −Ni x S y nanosheets with a length of approximately 400 nm and an average thickness of 33 nm are uniformly grown on the Ni foam. Benefiting from the unique 3D hierarchical structure and synergistic effect between Fe 0 and Ni x S y, the 3D Fe 0 −Nix Sy /NF hybrid shows an excellent electrocatalytic activity towards oxygen evolution reaction (OER) at extremely high current densities in basic media. The current densities of 1000 and 1500 mA cm −2 are achieved at low potentials of 1.57 and 1.60 V, respectively, thus meeting the expected OER standards for industrial applications. These overpotentials of the 3D Fe 0 −Nix Sy /NF hybrid are the lowest among all previously reported nickel‐sulfide‐based electrocatalysts, and are even superior compared to state‐of‐the‐art Ir/C catalysts. We further demonstrate that the integration of the 3D Fe 0 −Ni x S y /NF electrocatalyst as both anode and cathode with a silicon photovoltaic cell enables highly active and sustainable solar‐driven overall water splitting. Abstract : Time to split : 3D ultrasmall Fe 0 ‐coupled nickel sulfide nanosheets hybrid are synthesized for extremely efficient water oxidation in basic media.